Comparison of hearing outcome using ossiculoplasty with autologous incus versus titanium prosthesis - Gangadaran, Udayachandrika; S., Muthuchitra; S., Mary Nirmala; K., Ramya Devi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The aim of the study is to compare the efficacy of autologous incus versus allogenic titanium prosthesis in terms of anatomical results, hearing gain after surgery, operative course and complications. Methods: This is a prospective interventional study of 20 patients out of which 10 underwent autologus incus and 10 underwent titanium prosthesis ossiculoplasties performed between April 2018 To April 2019 in Government Kilpauk medical college and hospital, Chennai after ethical clearance. The postoperative improvement of mean air-bone gap and air conduction over same frequencies between the two groups were studied. A improvement in pure tone average more than 10 dB was considered successful. Results: In current study, 10 patients underwent ossiculoplasties using titanium ossicular replacement prosthesis and 10 patients underwent ossiculoplasties using autologous incus. 5 of the patients in each group underwent canal wall up and 5 underwent canal wall down procedure. The average ABG closure was 9.30 dB in incus group and 15.22 dB in titanium group. Conclusions: Titanium ossicular prosthesis ossiculoplasties provide a significant hearing gain and are advantageous because of the easy insertion with pre-sculpted structure yet the cost is a concern. Better results were noted in canal wall up procedures more than canal wall down procedures.